瀕死經驗與靈魂——回應關啟文: Near-Death Experience and Soul: A Response to Kwan Kai Man - LAU, Joe (International Journal of Chinese & Comparative Philosophy of Medicine, 2016)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. Do near-death experiences (NDEs) show that the soul exists? This paper argues that it is premature to draw such a conclusion, even if current science cannot fully explain all features of NDEs. Clear and univocal evidence is needed, but many reports of NDEs are problematic and subject to conflicting interpretations. In addition, many cases of NDEs took place in circumstances where residual neural activities could not be ruled out. Progress can be made with better experimental designs and brain imaging techniques. The paper concludes with a discussion of physicalism and its logical connections to out-of-body experiences. DOWNLOAD HISTORY | This article has been downloaded 151 times in Digital Commons before migrating into this platform.